Effect of dietary phenylalanine on growth performance and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) in low fishmeal diets - Zhang, Shuze; Wang, Chang’an; Liu, Siyuan; Wang, Yaling; Lu, Shaoxia; Han, Shicheng; Jiang, Haibo; Liu, Hongbai; Yang, Yuhong (Frontiers in Nutrition, 2023)
This study aimed to investigate the effects of phenylalanine on the growth, digestive capacity, antioxidant capability, and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) fed a low fish meal diet (15%). Five isonitrogenous and isoenergetic diets with different dietary phenylalanine levels (1.82, 2.03, 2.29, 2.64, and 3.01%) were fed to triplicate groups of 20 fish (initial mean body weight of 36.76 ± 3.13 g). The weight gain rate and specific growth rate were significantly lower (p < 0.05) in the 3.01% group. The trypsin activity in the 2.03% group was significantly higher than that in the control group (p < 0.05). Amylase activity peaked in the 2.64% treatment group. Serum superoxide dismutase, catalase, and lysozyme had the highest values in the 2.03% treatment group. Liver superoxide dismutase and catalase reached their maximum values in the 2.03% treatment group, and lysozyme had the highest value in the 2.29% treatment group. Malondialdehyde levels in both the liver and serum were at their lowest in the 2.29% treatment group. Interleukin factors IL-1β and IL-6 both reached a minimum in the 2.03% group and were significantly lower than in the control group, while IL-10 reached a maximum in the 2.03% group (p < 0.05). The tight junction protein-related genes occludin, claudin-1, and ZO-1 all attained their highest levels in the 2.03% treatment group and were significantly higher compared to the control group (p < 0.05). The intestinal villi length and muscle layer thickness were also improved in the 2.03% group (p < 0.05). In conclusion, dietary phenylalanine effectively improved the growth, digestion, absorption capacity, antioxidant capacity, and intestinal health of O. mykiss. Using a quadratic curve model analysis based on WGR, the dietary phenylalanine requirement of triploid O. mykiss fed a low fish meal diet (15%) was 2.13%.